Análise comparativa de métodos de carregamento de dados em GPU para multiplicação de matriz-vetor - Bossoni, Giovani (2023)
With the introdution of multicores processors, there is a new need to develop new algorithms capable of taking advantage of the parallelism from the new Hardware. This project porpose a comparative analysis between methods for data transfer between CPU and GPU and the impact on perfomance on computation of matrix-vector multiplication on CUDA plataform, Using three approaches: common, Unifed Memory and Streams, where the last one has shown gains from 10% to 35% in scenarios where there is a large amount of data.